Real-Time Tracking of Highly Luminescent Mesoporous Silica Particles Modified with Europium β-Diketone Chelates in Living Cells - Kim, Jong-Seok (Nanomaterials (Basel), 2021)
Highly luminescent europium complexes modified mesoporous silica particles (MSP) were synthesized as an imaging probes for both in-vitro diagnostic and in-vivo cellular tracking agents. Europium β-diketone chelates (4,4,4-trifluoro-l-(2-thienyl)-l,3-butanedione) trioctylphosphine europium (III) (Eu(TTA)(3)(P(Oct)(3))(3)) were incorporated inside the nanocavities that existed in hierarchical MSP (Eu@MSP). The MSP and Eu@MSP on mouse bone marrow-derived macrophages (BMDMs) did not show any toxic effect. The MSP and Eu@MSP in the BMDMs were found at cytoplasm without any degradation and immunogenicity. However, both pro- and anti-inflammatory cytokines of macrophages were significantly increased when lipopolysaccharide and a high concentration (100 μg/mL) of MSP and Eu@MSP were treated simultaneously.